Characteristics of nesting habitat of sea turtle Lepidochelys olivacea in Lhoknga Beach, Aceh Besar District, Indonesia - Hindar Hindar; Zainal A. Muchlisin; Faisal Abdullah (Syiah Kuala University, 2018)
The purpose of this study was to determine the characteristics of nesting habitat of sea turtle in Lhoknga beach. The observation was conducted at three locations from January to March 2016. The study showed that the coastal slope average ranges 1.03 ° - 1.38 °. The average of nest temperature was 28.05 °C to 29.47 °C (inside the nest) and from 28.77 ° C to 29.95 ° C (at the surface of the nest). The width beach at high tide ranges from 20.17 m to 21.83 m and 31 m to 33.83 m at low tide. The nest humidity ranges from 20.5% -24.15%. There were six species of coastal vegetation recorded during the study, where station 1 has higher of density and diversity of the coastal vegetation. In general, Lhoknga Beach is suitable for nesting of the sea turtle. A total of 13 sea turtles (Lepidochelys olivacea) were nesting during the study, where station 1 had higher of nesting frequency.